2017
DOI: 10.1016/j.ceb.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Golgi ribbon disassembly during mitosis, differentiation and disease progression

Abstract: The Golgi apparatus is tightly integrated into the cellular system where it plays essential roles required for a variety of cellular processes. Its vital functions include not only processing and sorting of proteins and lipids, but also serving as a signaling hub and a microtubule-organizing center. Golgi stacks in mammalian cells are interconnected into a compact ribbon in the perinuclear region. However, the ribbon can undergo distinct disassembly processes that reflect the cellular state or environmental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 121 publications
0
88
0
Order By: Relevance
“…The Golgi has been studied extensively in structure and function (Sütterlin and Colanzi 2010; Wang and Seemann 2011; Yadav and Linstedt 2011; Gosavi and Gleeson 2017; Wei and Seemann 2017). 3D-EM techniques made data available for the Golgi of plants (Staehelin and Kang 2008) and mammals (Ladinsky et al 1999; Marsh and Pavelka 2013; Koga et al 2017).…”
Section: Golgi Transitionmentioning
confidence: 99%
“…The Golgi has been studied extensively in structure and function (Sütterlin and Colanzi 2010; Wang and Seemann 2011; Yadav and Linstedt 2011; Gosavi and Gleeson 2017; Wei and Seemann 2017). 3D-EM techniques made data available for the Golgi of plants (Staehelin and Kang 2008) and mammals (Ladinsky et al 1999; Marsh and Pavelka 2013; Koga et al 2017).…”
Section: Golgi Transitionmentioning
confidence: 99%
“…The Golgi ribbon can undergo rapid remodelling events, such as in mitosis or the repositioning of the Golgi for directed migration . Golgi dynamics are regulated by membrane flux from the ER , and by interactions between the cytoskeleton and molecular scaffolds on Golgi membranes.…”
Section: Characterisation Of Golgi Structurementioning
confidence: 99%
“…Moreover, to address the specific role of the disassembly of Golgi membranes, Guizzunti and Seemann (2016) engineered cells to induce the formation of large diaminobenzidine‐based polymers in the Golgi lumen, with the result of inhibiting both Golgi cisternal unstacking and vesiculation. Under these conditions, the cells were able to enter into mitosis, but arrested in prometaphase with intact Golgi stacks that were clustered around a monopolar spindle, resulting in activation of the spindle assembly checkpoint (Guizzunti and Seemann, ; Wei and Seemann, ). Altogether, these findings revealed that the mitotic disassembly of Golgi stacks and the release of Golgi‐associated proteins are both required for spindle formation and progression to metaphase (Figure b and c).…”
Section: Coordination Of Golgi Fragmentation With the Cell Cyclementioning
confidence: 99%
“…In spite of its complex organisation, the GC can undergo rapid and highly dynamic modifications of shape and localisation under different physiological conditions (Yadav and Linstedt, 2011;Wei and Seemann, 2017). For example, during cell migration, the GC is relocated toward the direction of migration for sustaining cell movement (Bisel et al, 2008;Sutterlin and Colanzi, 2010).…”
Section: Introductionmentioning
confidence: 99%